2019
DOI: 10.1111/cen.13982
|View full text |Cite
|
Sign up to set email alerts
|

Fertility desires and reproductive needs of transgender people: Challenges and considerations for clinical practice

Abstract: The majority of transgender and gender nonconforming persons seeking medical care are of reproductive age. Hormonal treatment and sex reassignment surgery, which are used in the management of gender dysphoria, compromise fertility potential. Children and adolescents with gender dysphoria have specific treatment regimens starting with puberty-blocking medications. According to international guidelines, fertility preservation should be discussed before any hormonal treatment, although our knowledge on the reprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 87 publications
(113 reference statements)
0
26
0
Order By: Relevance
“…3 Having a child for TG individuals can be difficult because GAHT or GAS can compromise future fertility. 4 Currently, no sufficient data are available to evaluate the long-term reproductive effects of GAHT, the reversibility and the delay from discontinuation of GAHT to fertility recovery. In TG women, most studies reported cytological alterations of spermatogenesis leading to semen parameter alterations during GAHT with no specific data on the reversibility of GAHT's reproductive effects.…”
Section: Introductionmentioning
confidence: 99%
“…3 Having a child for TG individuals can be difficult because GAHT or GAS can compromise future fertility. 4 Currently, no sufficient data are available to evaluate the long-term reproductive effects of GAHT, the reversibility and the delay from discontinuation of GAHT to fertility recovery. In TG women, most studies reported cytological alterations of spermatogenesis leading to semen parameter alterations during GAHT with no specific data on the reversibility of GAHT's reproductive effects.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, a large portion of the transgender community believes that testosterone use represents a contraceptive measure. 3 In a cohort of 197 transgender men, 16% used testosterone as contraception, and 5.5% said health care providers had advised them this was a reliable method. 26 The total number of pregnancies in transgender men is unknown, but studies suggest that pregnancy rates range from 5% to 17% in adolescents and adults.…”
Section: Contraception and The Tgnc Patientmentioning
confidence: 99%
“…2 If an individual's gender identity does not fit within the male/female dichotomy, the description ''nonbinary gender identity'' can be applied. 3 Gender dysphoria is defined as the distress experienced when gender identity and designated gender are not completely congruent. 2 A TGNC person may choose to ''transition'' or change their physical, social, and legal characteristics to align with the identified gender.…”
Section: Introductionmentioning
confidence: 99%
“…8 Unfortunately, the treatment options to facilitate gender transition include medical interventions that can have deleterious effects on fertility. 10 Consequently, most TG people require assisted reproductive technologies (ART), which depend on many factors, such as the gender of the partner, the timing of the ART in relation to the GAMIs, and the legislation applicable in their country of residence. 11 Additionally, TG people are often also interested in the possibility of using fertility preservation.…”
Section: Introductionmentioning
confidence: 99%